Effectiveness of lavender aromatherapy in reducing dysmenore - Febrika Nanda; Hendrik Probo Sasongko (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Adolescence, which occurs between the ages of 11 and 20, is also a period of maturation of the human reproductive organs, also known as puberty. Menstruation is the most common problem experienced by teenagers today. Early menarche, lack of exercise, abnormal menstrual cycles, and alcohol consumption are some of the causes of dysmenorrhea. The World Health Organization reported in 2020 that 1,769,425 adolescent girls experienced dysmenorrhea (90%) of the total and 10%-15% of them experienced severe dysmenorrhea. In Indonesia, 64.25% of productive women experience menstrual pain. Purpose: To identify the effectiveness of lavender aromatherapy in reducing dysmenorrhea in adolescents. Method: This research was quantitative, with a pre-experimental design using a single-group pre-post test approach. The study was conducted MTS Mumbulsari Jember with 40 respondents. Data collection used purposive sampling and a Numeric Rating Scale (RRS) instrument to determine pain intensity and aromatherapy candles. Results: From the T-Test calculation with a p value of 0.000 < α (0.05), which means there is a relationship between lavender aromatherapy in reducing dysmenorrhea. Aromatherapy works by influencing the emotional center in the limbic system, providing a calming and relaxing effect on the body, which can reduce pain. Conclusion: Relaxation therapy with aromatherapy is recommended as a self-administered technique to treat dysmenorrhea, thereby reducing the use of analgesics. Suggestion: The results of this study are expected to be a reference for female students regarding non-pharmacological methods to reduce menstrual pain.